Peranan Wali Kota Medan dalam Meningkatkan Mutu Pendidikan - Yunita Lorenda, Sri; Tri Mawar Sianturi; Devi Natalia Hutagalung; Pretty Marpaung, Yolanda (VISA: Journal of Vision and Ideas, 2024)
This research aims to determine the role of the mayor of Medan in improving the quality of education in the city of Medan. The research methods used are library methods and quantitative methods. The results of the research show that the role of the mayor of Medan has gone well in improving the quality of education in the city of Medan. By providing scholarships carried out by the mayor of Medan